تأثير استخدام تقانة المعلومات في جودة الخدمات الالكترونية : دراسة استطلاعية لآراء عينة من العاملين في المصارف (الموصل و الاندلس و الشرق الأوسط ) للتنمية و الاستثمار في محافظة نينوى - هبة محمد حسين الطائي; نور ضياء عزيز الصفو (PROSPECTIVE RESEARCHES, 2023)
Modern organizations face drastic changes in the technological aspect makes adaptation with it something inevitable, as competition is intensified on the production of goods and services. The objective of this research is to identify the impact of information technology on the quality of electronic services in banks (Mosul, Andalusia and the Middle East) in the province of Nineveh. To achieve this objective, a questionnaire has been designed and distributed to the research sample of (40) individuals, (36) of them are analyzed. Using the statistical analysis SPSS. The research comes up with a series of conclusions which confirm the existence of a correlation effect Manuetin between the variables of research and investment. The researchers recommend the adoption of information technology to provide efficient electronic services in the banks surveyed by selecting and identifying key dimensions that should be available in the electronic service to provide high quality and lead to satisfy customers' needs and desires.